The Influence Of Auditor Competence On Audit Quality In Agencies Government - Arman Jaya Ndruru; Gunawan Syahputra Siburian; Nofatrio Soarota Zebua; Rizky Chairuddin Sembiring Meliala; Fitri Yani Panggabean (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to analyze the effect of auditor competence on audit quality in government agencies, focusing on internal auditors operating in various government agencies. The method used in this study is multiple regression analysis, which involves data collection through questionnaires distributed to auditors in several agencies. The results of the study indicate that auditor competence has a positive and significant effect on audit quality. Specifically, competence that includes the knowledge, skills, and experience of auditors has been shown to increase the effectiveness and efficiency of the audit process, as well as the reliability of the audit results produced. The results of data analysis using the linear regression method indicate that auditor competence has a positive and significant effect on audit quality. Auditors with higher education levels, broader work experience, and professional certifications tend to produce higher-quality audits. Additionally, continuous training has been proven to contribute to enhancing auditors' abilities to address the complexities of auditing in government institutions.